Instrument processing knowledge and practice amongst healthcare workers in Addis Ababa, Ethiopia - Geberemariyam, Biniyam Sahiledengle (International Journal of Infection Control, 2018)
The recent outbreaks of healthcare associated infections (HAIs) as a result of poor cleaning, disinfection and sterilization of medical equipment, and concerns about the possible spread of highly contagious infections has brought the issue of instrument processing in the fore front of infection prevention. Conversely, in many developing countries such as Ethiopia instrument processing practice (IPP) among healthcare workers (HCWs) is not quantified yet. A cross-sectional study was conducted to assess HCWs instrument processing practice and associated factors in health centers of Addis Ababa, Ethiopia in January, 2017. Simple random sampling technique was employed to select 328 HCWs. Data was collected using structured questioner and checklist. Univariate analysis, binary and multivariate logistic regression was computed. Adjusted odds ratio (AOR) with corresponding 95% confidence interval (CI) was used to quantify the strength of association and p-value ≤ 0.05 was used to declare statistical significance. Less than half 46.3% (95%CI: 40.9, 51.5) of HCWs are knowledgeable on instrument processing and 220(67.1%) (95%CI: 61.9, 71.6) of HCWs had safe IPP. High risk perception towards transmitting an infection while working (AOR: 5.35; 95%CI: 2.44, 11.73), being knowledgeable on instrument processing (AOR: 2.81; 95%CI: 1.50, 5.27), and having positive attitude towards infection prevention (AOR: 2.39; 95%CI: 1.19, 4.84) were the most important variables associated with safe IPP. In general, HCWs instrument processing practice was not safe enough. Moreover, significant number of HCWs lacks adequate instrument processing knowledge. Hence, enhancing HCWs awareness on IPP should be undertaken along with urgent improvement in routine monitoring of autoclaves. Keywords: Instrument processing; Decontamination; Cleaning; Sterilization; Disinfection; Reusable medical devices; Ethiopia